Information access and needs of patients in palliative care and their family members during hospital discharge - Mäkelä, Marjo; Hupli, Maija; Kuusisto, Anne (Finnish Journal of eHealth and eWelfare, 2023)
Responding to information needs is a significant way to improve the successful discharge of the patient and his family member and the best possible end-of-life care. As the number of patients in palliative care increases, the development of guidance is essential to ensure the quality of care. The purpose of this study was to describe patients in palliative care and their family member’s access to information and needs during and after discharge from the hospital. The method was a scoping review. A systematic data search was done to two databases (PubMed and CINAHL) in September 2021 and the searches were was updated in August 2022 and September 2023. The search was completed manually. There was a total of 1,132 search results, of which 14 articles were selected for the literature review after inclusion and exclusion criteria. Most of the studies were qualitative studies (12), one mixed-method study and one quantitative study. Patients in palliative care and their family members felt that they had received information about the disease and guidance for survival at home. Information needs were related to disease prognosis, symptoms and treatment, health care services, support for survival at home and the flow of information. The information needs of patients and family members were different. Patients and family members have stressed the individuality, repeatability and comprehensibility of information needs at the time of discharge and after. The separate information needs of family members and patients should be recognized and considered in guidance. Continuity of care should be secured by cooperation between professionals and by utilizing different data transfer methods.